Developmental dynamics of the neural crest-mesenchymal axis in creating the thymic microenvironment - Handel, A; Cheuk, S; Dhalla, F; Maio, S; Hübscher, T; Rota, I; Deadman, M; Ekwall, O; Lutolf, M; Weinberg, K; Hollander, G (American Association for the Advancement of Science, 2022)
The thymic stroma is composed of epithelial and non-epithelial cells providing separate microenvironments controlling homing, differentiation and selection of hematopoietic precursor cells to functional T cells. Here we explore at single cell resolution the complex composition and dynamic changes of the non-epithelial stromal compartment across different developmental stages in the human and mouse thymus, and in an experimental model of the DiGeorge syndrome, the most common form of human thymic hypoplasia. The detected gene expression signatures identify novel stromal subtypes and relate their individual molecular profiles to separate differentiation trajectories and functions revealing an unprecedented heterogeneity of different cell types that emerge at discrete developmental stages, and vary in their expression of key regulatory signalling circuits and extracellular matrix components. Taken together, these findings highlight the dynamic complexity of the non-epithelial thymus stroma and link this to separate instructive roles essential for normal thymus organogenesis and tissue maintenance.